Phytonanofabrication of iron oxide particles from the Acacia jacquemontii plant and their potential application for the removal of brilliant green and Congo red dye from wastewater - Patel, Shreya; Desai, Reema; Patel, Bhakti; Ali, Daoud; Dawane, Vinars; Gadhvi, Kamlesh; Yadav, Virendra Kumar; Choudhary, Nisha; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Bioengineering and Biotechnology, 2023)
Phytonanofabrication is one of the most emerging areas that has drawn the attention of scientists throughout the globe due to its eco-friendly nature, and biocompatibility. In the current investigation, investigators have reported the phyto-assisted formation of iron oxide nanoparticles (IONPs) from a rare species of Acacia (Acacia jacquemontii). Firstly, ethanolic extracts of the stem powder were analyzed by high-performance thin-layer chromatography (HP-TLC) for the identification of the phytochemicals in the stem sections of Acacia. Further, IONPs were synthesized by chemical co-precipitation method by using stem extract. The phytonanofabricated iron oxide particles (IOP) were investigated by UV-Vis spectroscopy, Fourier transforms infrared (FTIR), an X-ray diffraction pattern (XRD), Field emission scanning electron microscope (FESEM), and electron diffraction spectroscopy (EDS) for elemental analysis. The HPTLC confirmed the presence of several phenols, and terpenoids in the ethanolic extracts of the stem. UV-Vis exhibited an absorbance peak at 380 nm indicating the formation of IONPs, while the FTIR showed the typical bands for Fe-O in the range of 599-1000 cm -1 in addition to several functional groups of organic molecules at 1596 cm -1 , 2313 cm -1 , and 3573 cm -1 . XRD exhibits the amorphous nature of IONPS with peaks at 30.7, 35.5, and 62.7° (Chen et al., 2020b). The IONPs were spherical-shaped whose size varies from 10-70 nm as confirmed by FESEM. EDS exhibited the presence of Fe, O, C, and Na, Cl.Finally, the phytonanofabricated iron oxide particles were utilized for the removal of brilliant green and Congo red dye from the aqueous solution. The removal efficiency of BG dye was up to 54.28% while of CR dye was up to 36.72% in 120 minutes and 60 minutes respectively.Further, the effect of pH and contact time was also assessed on both the dyes where, CR exhibited maximum removal at acidic pH i.e., 47.5% while BG showed maximum removal at 10 pH i.e., 76.59%.